PENGARUH METODE KUIS TIM TERHADAP HASIL BELAJAR IPA SISWA KELAS V UPTD SD NEGERI 122381 PEMATANG SIANTAR - Damanik, Elseria; Purba, Natalina; Sitohang , Sukardo (Universitas Katolik Santo Thomas Medan, 2023)
ABSTRACT This study aims to determine the effect of applying the team quiz method to the science learning outcomes of fifth grade students at UPTD SD Negeri 122381 Pematang Siantar on theme 8 sub-theme 2. There are 2 hypotheses in this study namely, (1) there is an effect of applying the team quiz method to learning outcomes Science class V students (H1) and (2) there is no effect of applying the team quiz method to the science learning outcomes of class V students (H0). The method used in this study is an experimental method with a pre-experimental research design with a one group pre-test post-test design. The number of samples in this study were 24 people. Data collection was carried out by conducting tests, observation and documentation, the research data obtained was analyzed using statistical analysis. Based on the results of the T-test data analysis, it is known that the tcount is 10.4 while the ttable is 1.714 with a significance level of 0.05. So from saying that tcount > ttable. Based on the results of the analysis of the data obtained, it can be concluded that there is an influence of the team quiz method on the science learning outcomes of class V UPTD SD Negeri 122381 Pematang Siantar. This means H1 is accepted and H0 is rejected.